The Relationship between Age, Parity and Husband's Support and the Selection of Long-term Contraception Method (MKJP) By Woman of Childbearing Age - Windi Kusuma, Elsa; Eko Wardani, Hartati; Hapsari, Anindya (KnE Life Sciences, 2021)
The high birth rate of Indonesia has become a significant problem and requires special attention. As an effort to tackle the rapid population growth, the government has formulated a number of development and family planning programs. For instance, the National Family Planning programmes, which is mainly directed towards the use of the Long-term Contraception Method (MKJP); however, the actual usage rate of the programme is still low. This research aimed to examine the relationship between age, parity and husband’s support, and the MKJP selection by women of childbearing age in the working area of Dinoyo Public Health Centre, Malang City. This study was an analytical research with a cross-sectional design. The samples in this research were chosen through the purposive sampling method, with a total sample of 45 women. Data were collected through interviews and questionnaires. Data analysis was carried out using the Chi-Square test, with a significance level of < 0.05. The results showed that there was no significant relationship between the age and the selection of MKJP (sig. 0.461), between the parity and the selection of MKJP (sig. 0.522), and between the husband’s support and the selection of MKJP (sig. 0.460). Therefore, we conclude that there is no significant relationship between the age, parity and husband’s support, and the selection of MKJP by women of childbearing age in the working area of Dinoyo Public Health Centre. Keywords: age, parity, husband’s support, long-term contraception methods